2003
DOI: 10.1034/j.1600-0455.2003.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Disease. Contrast-Enhanced 3D Mr Angiography of the Lower Leg and Foot Compared with Conventional Angiography

Abstract: Purpose:  To determine whether contrast‐enhanced 3D MR angiography (CE MRA) could replace digital subtraction angiography (DSA) for the evaluation of atherosclerotic peripheral vascular disease of the lower leg and foot. Material and Methods:  Thirty‐five patients with symptoms of atherosclerotic disease of the leg were examined prospectively with CE MRA of the foot and the lower legs as well as with DSA from the aorta to the pedal arches. The MRA technique was focused on optimal imaging of the arteries of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
4
19
0
1
Order By: Relevance
“…As yet only a few studies have investigated the accuracy of pedal CE‐MRA in comparison with DSA (4, 6, 10, 11, 25). Kreitner et al (4) showed in a study involving 24 diabetic patients that the pedal arch vessels were identified significantly more often on MR angiograms than on DSA images (22 [92%] of 24 feet vs. 9 [38%] of 24 feet).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As yet only a few studies have investigated the accuracy of pedal CE‐MRA in comparison with DSA (4, 6, 10, 11, 25). Kreitner et al (4) showed in a study involving 24 diabetic patients that the pedal arch vessels were identified significantly more often on MR angiograms than on DSA images (22 [92%] of 24 feet vs. 9 [38%] of 24 feet).…”
Section: Discussionmentioning
confidence: 99%
“…Based on their findings, Hofmann et al (10) questioned whether DSA should still be considered a standard of reference. However, Cronberg et al (11), in a study conducted in 35 consecutive patients with PAOD, found that whereas CE‐MRA yielded a sensitivity of 92% for the detection of significant stenosis in the crural and pedal vessels when compared with DSA as the standard of reference, the specificity was only 64%. They therefore concluded that while CE‐MRA can be considered a useful diagnostic adjunct, it should not replace DSA as a standard of reference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(8–15) for the hands and from Refs. (16–24) for the feet. Another approach studied previously but not included in the tables is one using high frame rate 2D acquisition (25, 26).…”
Section: Summary Of Performance Parameters For Contrast‐enhanced Mr Amentioning
confidence: 99%
“…The major risk factors for PAD are older age (>40 years), cigarette smoking and diabetes mellitus (2). Patients diagnosed with PAD suffer from a limitation in exercise capacity and reduced quality of life, and are at increased risk of cardiovascular-associated morbidity and mortality (3,4).…”
Section: Introductionmentioning
confidence: 99%